Peran Arsitektur dan Antropologi dalam Tata Ruang Kota Indonesia Abad 21 - Gunawan Tjahjono (Antropologi Indonesia, 1999)
This paper attempts to examine various aspects of urban space design to be considered for policy making. Based upon his personal experience in conducting research with anthropologists in traditional environment , the author suggest that architects and anthropologists can contribute considerably to overcoming urban problem...[...] urban spaces that are prone to riot and other mass acts of violence indicate problems in urban policy. In the past, the citizens' culture determined urban form; but large cities are marked by cultural diversity. Whereas urban space is a field studied by urban planners and architects, culture is focus of anthropologists, who have largely been excluded from the urban policy making process. As a result, policy makers determined urban form according to their own cultural biases, without considering the cultural tendencies of the citizens.